Ներըմբռնողականությունը Հովհաննես Թումանյանի կյանքում - Հովհաննիսյան, Սուսաննա (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Ованес Туманян был в значительной степени наделен интуитивным восприятием причинно-следственных связей явлений и реалий. Ему были доступны сложные ощущения подсознательного мира, благодаря чему интуиция и предвидение стали существенными составляющими мировоззрения и миропонимания поэта, важными средствами познания мира. Hovhannes Tumanyan was largely endowed with an intuitive perception of the cause-and-effect relationships of phenomena and realities, as well as telepathic abilities. Complex sensations of the subconscious world were available to him, thanks to which intuition and foresight became essential components of the poet’s worldview and world perception, became important means of knowing the world.
Keywords: Գրականագիտություն